International Marketing Strategies for Small Luxury Business : LaSphera Case Study - Voráček, David; Machek, Martin; Stříteský, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The aim of this paper is to develop an international luxury marketing mix for the LaSphera brand, by incorporating the company’s international ambitions, its desired luxury brand positioning, as well as the perspective of a resource constrained and brand awareness lacking startup company. In order to achieve this aim, the Thesis first presents an extensive review of the most relevant theoretical concepts and frameworks, which lays the foundation for the subsequent practical analysis. Key findings and frameworks from the theoretical section, combined with the primary information provided by LaSphera, result in a comprehensive formulation of the 4 Ps of marketing. The developed marketing mix conceptualizes LaSphera’s existing marketing elements and considerations, while simultaneously expanding on them with new findings and recommendations
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses